The Effect Of Watermelon On Lowering Blood Pressure In Pregnant Women With Hypertension In Complex Cases In Campaka Purwakarta In 2026 - Metaliasari; Tia Nurfitri (International Journal of Health and Pharmaceutical (IJHP), 2026)
Pregnancy with risk high , such as hypertension , can cause more complications​ big for mother and fetus​​ during pregnancy , childbirth and postpartum More from 90 percent death Mother caused by complications obstetrics during pregnancy , childbirth , and postpartum . Consumption fruit watermelon can lower pressure blood High . A pre-experimental study with a one-group pretest-posttest design examined the effect of watermelon supplementation on pregnant women with hypertension. Thirty respondents were selected using total sampling. The pregnant women were given an intervention involving watermelon consumption for 7 days.The results of the statistical test prove that based on the Wilcoxon Signed Rank Test output , the systolic blood pressure value is Z = -4.784, while the diastolic blood pressure value is Z = -4.649 with an Asymp.Sig (2-tailed) value of 0.000. Because the p value <0.05, it can be concluded that there is a statistically significant difference between systolic and diastolic blood pressure before and after the intervention.